Analisis Hidraulika Jaringan Pipa PDAM Tirta Dharma dengan Sistem Komputasi - Meilani Belladona (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2015)
The purpose of the research was to analyze the distribution pipe network system water TAPS Tirta Dharma by using the program EPANET 2.0. Clean water services are managed by TAPS Tirta Dharma is already reaching out to most areas of the city, most of the customers comes from households. The number of clean water distribution of households in 19.209 KK of 4.606.370 m3 per year. Bengkulu City TAPS new could produce as much as 17.280.000 ltr/hr, so it still required an increase in production capacity by as much as 18.797.200 lt/hr, or 217,56 lt/sec. The problem examined is how the distribution pipe network system water TAPS Tirta Dharma by using the program EPANET 2.0? The methods used for this research consists of methods of data collection and data analysis methods. Data required primary data consist of i.e. the measurement of water pressure on metered houses and spread a detailed questionnaire. Secondary data are also needed to support research the research of map data network, water consumption data by the customer and other supporting data. Data obtained processed with hydraulics analysis either manually or in a simple statistical analysis and computation. Based on the results of the analysis it is known that water needs for housing in Surabaya already meet. Based on the results of the interviews can be noted that most of the people still using Shaved River Subdistrict shallow wells as a source of clean water.